Quality of life in functional rhinoplasty: rhinoplasty outcomes evaluation German version (ROE-D) - Bulut, Cem; Plinkert, Peter K.; Wallner, Frank; Baumann, Ingo (European archives of oto-rhino-laryngology and head & neck, 2016)
The aim of this study was to validate a German version of the rhinoplasty outcomes evaluation (ROE) questionnaire. A prospective study was conducted and a German translated ROE (ROE-D) questionnaire administered to 100 patients preoperatively, 6 and 12 months postoperatively. The translation was performed according to internationally accepted guidelines. To validate this instrument, we evaluated its reliability, validity and sensitivity. ROE-D was completed by 54 patients after 6 months and by 69 patients 1 year after functional rhinoplasty. Cronbach’s α indicated good internal consistency. Reliability was tested with a split-half-reliability, showing significant correlation. Discrimination validity was demonstrated by a comparison with healthy controls. Sensitivity to change showed medium to large effects. ROE-D is a reliable, validated and sensitive German instrument for measuring health-related quality of life in patients after rhinoplasty. The ROE-D focuses mainly on the aesthetic aspects of the rhinoplasty surgery.
Gesehen am 25.05.2020